Factors Hindering Tax Law Enforcement in the UMKM - Geby Mailan; Reynold Simanjuntak (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
This article discusses the inhibiting factors in tax law enforcement in the UMKM sector in Indonesia, focusing on complex regulations, lack of tax understanding and awareness, and limited use of technology. This study shows that UMKM are often hampered by complicated and frequently changing tax regulations, which leads to uncertainty and confusion in fulfilling tax obligations. In addition, a lack of understanding of the tax system and a low awareness of the importance of tax compliance exacerbate this problem. Not only that, the limitations in the use of digital technology in the UMKM sector also worsen the effectiveness of tax administration. As a result, many UMKM tend to avoid their tax obligations. This study uses a descriptive qualitative approach by examining literature and data from various relevant sources to understand this issue more deeply. In order to overcome these obstacles.